Kajian Kriminologi Terhadap Aksi Pencurian Kendaraan Bermotor Roda Dua - Mahinano, Ririn; Adam, Sherly; Lewerissa, Yanti Amelia (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The crime of theft of two-wheeled motor vehicles is a crime against property that is not uncommon in developing countries. However, the level of public awareness of the importance of protecting personal property is often ignored, so there are easily many opportunities for criminals to carry out their evil actions.Purposes of the Research: to study and discuss the factors causing the theft of two-wheeled motor vehicles in the jurisdiction of the Ambon Island Police and Lease Islands. As well as to review and discuss the efforts of the Ambon Island Police and Lease Islands in handling the theft of two-wheeled motorized vehicles.Methods of the Research: In this study is empirical juridical. Research location of the Ambon Island Police and Lease Islands. Population is the entire research unit that will be researched and then analyzed, Sample is the set of the population, Respondents are people who will answer questions asked by researchers for research purposes. The data source used is primary data and secondary data. Data collection techniques are carried out by interviews and documentation studies. Data analysis techniques are carried out qualitatively.Results of the Research: Shows that the factors causing the theft of two-wheeled motorized vehicles in the jurisdiction of the Ambon Island Police and Lease Islands are: The economic factor is the most influencing factor so that a person can commit a crime. The educational factor, when associated with the background of the crimes committed, is that the average perpetrator has low education. Environmental factors, whether good or bad, a person's behavior is strongly influenced by his social environment. The factor of negligence of users of two-wheeled motorized vehicles, crime of theft often arises due to the negligence of the user himself, for example by forgetting to lift the key, not locking the motor starter and others. -Lease islands namely: Preemptive efforts are the initial efforts made by the police to prevent the occurrence of the crime of theft of two-wheeled motorized vehicles, preventive efforts are carried out to prevent crimes from occurring. Meanwhile, repressive efforts are efforts to take action in the form of arrests for further legal proceedings against perpetrators who commit theft of two-wheeled motorized vehicles.